In vitro antibacterial activity of medicinal plant extracts against Escherichia coli strains from human clinical specimens and interactions with antimicrobial drugs - Ushimaru, P. I. [UNESP]; Barbosa, L. N. [UNESP]; Fernandes, A. A. H. [UNESP]; Di Stasi, L. C. [UNESP]; Fernandes Junior, A. [UNESP] (Taylor & Francis Ltd, 2012)
The biological properties of medicinal plants have been documented worldwide for many centuries. We aimed to evaluate interactions between crude extracts from Psidium guajava, Zingiber officinale, Cymbopogon citratus, Caryophyllus aromaticus, Mikania glomerata and Allium sativum samples and antimicrobial drugs against Escherichia coli strains. The susceptibility test performed was disc diffusion, and crude extracts were diluted (% v/v) into Muller-Hinton agar (MHA) at one quarter of the minimal inhibitory concentration for 90% (MIC90%) of E. coli strains found previously. Synergistic interactions were observed between C. citratus and polymyxin, and A. sativum extracts and gentamicin. The crude A. sativum extract was the only one that did not show any antagonism with the antimicrobial drugs. The results thus showed the potential use of these medicinal plants against E. coli strains, although antagonism with antimicrobial drugs is a negative aspect in the combined therapy of infectious diseases caused by E. coli.
Keywords: antibacterial activity; antimicrobial drugs; medicinal plants; synergism